Morphologic and Molecular Features of Hepatocellular Adenoma with Gadoxetic Acid-enhanced MR Imaging - Ba-Ssalamah, A (2015)
Purpose To evaluate the diagnostic performance of imaging features of gadoxetic acid-enhanced magnetic resonance (MR) imaging to differentiate among hepatocellular adenoma (HCA) subtypes by using the histopathologic results of the new immunophenotype and genotype classification and to correlate the enhancement pattern on the hepatobiliary phase (HBP) with the degrees of expression of organic anion transporting polypeptide (OATP1B1/3), multidrug resistance-associated protein 2 (MRP) (MRP2), and MRP 3 (MRP3) transporters. Materials and Methods This retrospective study was approved by the institutional review board, and the requirement for informed consent waived. MR imaging findings of 29 patients with 43 HCAs were assessed by two radiologists independently then compared with the histopathologic analysis as the standard of reference. Receiver operating characteristic curves and Spearman rank correlation coefficient were used to test the diagnostic performance of gadoxetic acid-enhanced MR imaging features, which included the retention or washout at HBP and degree of transporter expression. Interreader agreement was assessed by using the κ statistic with 95% confidence interval. Results The area under the curve for the diagnosis of inflammatory HCA was 0.79 (95% confidence interval: 0.64, 0.90); for the steatotic type, it was 0.90 (95% confidence interval: 0.77, 0.97); and for the β-catenin type, it was 0.87 (95% confidence interval: 0.74, 0.95). There were no imaging features that showed a significant statistical correlation for the diagnosis of unclassified HCAs. On immunohistochemical staining, OATP1B1/3 expression was the main determinant for the retention, whereas MRP3 was the key determinant for washout of gadoxetic acid at HBP (P < .001). MRP2 appeared to have no role. Conclusion Gadoxetic acid-enhanced MR imaging features may suggest the subtype of HCA. The degree of OATP1B1/3 and MRP3 expression correlated statistically with gadoxetic acid retention and washout, respectively, in the HBP. (©) RSNA, 2015 Online supplemental material is available for this article.